CURRENT ISSUES OF DEVELOPING YOUTH SPIRITUALITY IN THE CONTEXT OF GLOBALIZATION (Spectrum Journal of Innovation, Reforms and Development, 2026)
This article examines the contemporary problems of developing youth spirituality under conditions of globalization. The analysis proceeds from a broad understanding of spirituality as a system of values, meanings, moral self-regulation, cultural memory, social responsibility, and the capacity for reflective life orientation. Globalization has expanded young people’s access to education, information, intercultural communication, and civic participation, yet it has also intensified identity fragmentation, digital dependency, value relativism, consumer pressure, inequality, and psychological vulnerability.